Mental planes - Titone, Jennifer, author; Sullivan, Patrice, advisor; Osborne, Erika, advisor; Ryan, Ajean, committee member; Bohn, Andrea, committee member (Colorado State University. Libraries, 2014)
My works are mental planes in which I chart the accounts and associations I have with textiles and patterned objects. Each piece is a direct consequence of being raised within a family of industrial textile manufactures that produced fabrics for fashion, food, and bio-medical science industries. While I do not know the technicalities that exist within the process of designing and creating fabric-based materials and ornamentations, my daily exposure to the industrial craft has instilled an inherent sensibility for textiles and related objects of pattern that I come in contact within my daily encounters. Painting in an abstract manner that mimics collage, I incorporate the synthetic, the flat, and the vagaries within representational forms. This encourages intentional ambiguity within synthesized spaces, causing the viewer to struggle and grasp to make a connection. The viewers are invited into the puzzle to create their own narratives of place and time.